Understanding XPO1 Target Networks Using Systems Biology and Mathematical Modeling - Muqbil, Irfana; Kauffman, Michael; Shacham, Sharon; M. Mohammad, Ramzi; S. Azmi, Asfar (Current Pharmaceutical Design, 2014)
The nuclear transport protein Exportin 1 (XPO1), also called chromosome region maintenance 1 (CRM1), is over-expressed 2- 4 fold in cancer. XPO1 is one of seven nuclear exporter proteins, and is solely responsible for the transport of the major tumor suppressor proteins (TSPs) from the nucleus to the cytoplasm. XPO1 exports any protein that carries a leucine-rich, hydrophobic nuclear export sequence (NES). A number of inhibitors have been discovered that block XPO1 function and thereby restore TSPs to the nucleus of both malignant and normal cells. However, natural product, irreversible XPO1 antagonists such as leptomycin B (LMB) have proven toxic in both preclinical models and in the clinic. Recently, orally bioavailable, drug-like small molecule, potent and selective inhibitors of XPO1 mediated nuclear export (“SINE”) have been designed and are undergoing clinical evaluations in both humans and canines with cancer. The breadth of clinical applicability and long-term viability of an XPO1 inhibition strategy requires a deeper evaluation of the consequence of global re-organization of proteins in cancer and normal cells. Unfortunately, most of the studies on XPO1 inhibitors have focused on evaluating a limited number of TSPs or other proteins. Because XPO1 carries 220 mammalian proteins out of the nucleus, such reductionism has not permitted a global understanding of cellular behavior upon drug-induced disruption of XPO1 function. The consequence of XPO1 inhibition requires holistic investigations that consider the entire set of XPO1 targets and their respective pathways modulated without losing key details. Systems biology is one such holistic approach that can be applied to understand XPO1 regulated proteins along with the downstream players involved. This review provides comprehensive evaluations of the different computational tools that can be utilized in the better understanding of XPO1 and its target. We anticipate that such holistic approaches can allow for the development of a clinically successful XPO1 targeted therapeutic strategy against cancer.
Keywords: network medicine